Immunoliposomes: a new therapeutic option to treat SynGAP1-associated epilepsy - Wienken, Katharina; Mazur, A.; Gericke, Birthe; Petralla, Sabrina; Wagner, Lelia; Seifert, O.; Kontermann, R. E.; Fricker, Gert (European journal of pharmaceutics and biopharmaceutics, 2025)
The blood-brain barrier (BBB) hinders the uptake of most drugs into the brain. Thus, active processes, physiologically necessary for nutrient uptake, like receptor-mediated transcytosis have become popular targets for drug transport. One such receptor is the transferrin receptor 1 (TfR), being highly expressed at the BBB. Immunoliposomes targeting the TfR were loaded with rosuvastatin to improve the therapy of SynGAP1-associated epilepsy. The rational of using rosuvastatin is based on its function downregulating the Ras-Raf-MEK-ERK pathway, which is upregulated in excitatory neurons in patients with SynGAP1-related disorders. However, rosuvastatin shows poor BBB permeability. Therefore, immunoliposomes decorated with anti-TfR antibody Ox26 and its single-chain variable fragment (scFv) were prepared and characterized. Immunoliposomes could be prepared reproducibly with a size of about 125 nm, were not hemolytically active and showed colloidal stability in plasma for 2 h. They exhibited a high uptake into endothelial cells which was not altered in presence of the natural ligand transferrin. In vivo application of fluorescently labeled immunoliposomes demonstrated a long plasma half-life and accumulation in brain capillaries. In comparison to unmodified liposomes, Ox26- and scFv-immunoliposomes showed a 2.8- and 2.5-fold improved transfer of rosuvastatin into brain tissue, suggesting successful passage of the BBB.